A transient, flat spectrum radio pulsar near the Galactic Centre. Issue 2 (9th March 2017) - Dexter, J.; Degenaar, N.; Kerr, M.; Deller, A.; Deneva, J.; Lazarus, P.; Kramer, M.; Champion, D.; Karuppusamy, R.
Abstract: Recent studies have shown possible connections between highly magnetized neutron stars ('magnetars'), whose X-ray emission is too bright to be powered by rotational energy, and ordinary radio pulsars. In addition to the magnetar SGR J1745−2900, one of the radio pulsars in the Galactic Centre (GC) region, PSR J1746−2850, had timing properties implying a large magnetic field strength and young age, as well as a flat spectrum. All characteristics are similar to those of rare, transient, radio-loud magnetars. Using several deep non-detections from the literature and two new detections, we show that this pulsar is also transient in the radio. Both the flat spectrum and large amplitude variability are inconsistent with the light curves and spectral indices of three radio pulsars with high magnetic field strengths. We further use frequent, deep archival imaging observations of the GC in the past 15 yr to rule out a possible X-ray outburst with a luminosity exceeding the rotational spin-down rate. This source, either a transient magnetar without any detected X-ray counterpart or a young, strongly magnetized radio pulsar producing magnetar-like radio emission, further blurs the line between the two categories. We discuss the implications of this object for the radio emission mechanism in magnetars and for star and compact object formation in the GC.